RESEARCH ON MOTOR BEHAVIOR IN THE YEAR 2018 - Leandro Nogueira Dutra; Matheus Henrique Santos Lucas; Arthur Moreira Ferreira; Cíntia de Oliveira Matos; Brenner Ottero; Madson Pereira Cruz; André Rodrigues de Oliveira Neto; Herbert Ugrinowitsch (Journal of Physical Education)
ABSTRACT Motor Behavior (MB) is the study of neuropsychological processes with regard to the motor response organization in terms of learning, control, and motor development. Three research sub-areas emerged from MB, that is, Motor Learning (ML), Motor Control (MC), and Motor Development (MD). The present study aimed at describing the intellectual production related to ML, MC and MD sub-areas in 2018, in addition to identifying the current profile of the MB area. The intellectual production of the MB sub-areas was organized according to stratum, type of task, and adherence to the journals of area 21 (CAPES). Fifty three articles on MB, published by 51 researchers, were found. All these studies were produced by the Graduate Programs of Physical Education in 2018. The distribution of the articles in sub-areas was represented as follows: 30.18% ML, 54.72% MC, and 15.10% MD. The MC sub-area had 86% of its articles published in the upper strata; the ML sub-area had 37%, followed by the MD sub-area with 13%. The average of the three sub-areas resulted in 83.02% of studies with simple tasks and only 16.98% with complex tasks. The greater number of publications with low adherence combined with the greater number of investigations with simple tasks seems to show the researchers' difficulty in approaching the knowledge produced in the MB area for undergraduate Physical Education students.